Opportunities and Challenges in Applying Solid-State NMR Spectroscopy in Organic Mechanochemistry - Silva, Igor d'Anciães Almeida (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.